A biomechanical analysis for proficient and less-proficient subjects for soccer heading - Hernandez, L. C. B.; Chen-Hua, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Soccer is one of the most popular sports and is played and watched by millions of people around the world. In heading the players intentionally strike the ball using his head; therefore it is essential to instruct them in a proper manner how to do it optimally. Our results showed that lower and upper body had a significant difference between the proficient and less proficient subjects. For upper body kinematics, the proficient subjects exerted lesser elbow angles (47.8" (1.9) than the less-proficient (58.7"(3.5)). In the case of lower bdy kinetics, the proficient subjects exerted greater ankle moment (l.g(O.2) NmlKg) than less proficient subjects (1.5(0.3)Nm/Kg). With the results obtained it became possible to create particular training programs on how to perform a skill better and therefore result in an improvement of their ability.